REPORT CASE OF EXCESSIVE GENITAL WARTS, WAD MADANI MATERNITY HOSPITAL - Alhassan, Elhasan Mohamed; Abdel Hafiz, Abderhman; El Imam, Mohamed; Miskeen, Elhadi (Gezira Journal of Health Sciences, 2009)
Anogenital warts (condylomata acuminata) is the most common viral sexually transmitted disease in the United States. Although condylomata affect both genders, data from office visits for warts obtained from the 1994 to 1998 National Ambulatory Medical Care Survey showed that women accounted for 67 percent of the patient population (1).